Molecular phylogeny of Onobrychis sect. Onobrychis (Fabaceae-Hedysareae) with insights into its taxonomy and character evolution - Hadadi, Anahita; Kaveh, Akram; Nafisi, Hanyieh; Kazempour-Osaloo, Shahrokh (Phytotaxa, 2023)
Onobrychis sect. Onobrychis, as the most species-rich section of the genus Onobrychis, ranges from Central Asia to Europe with a south extension into North Africa. In this study, we concentrated on the systematics of previously poorly represented O.sect. Onobrychis using a substantial taxon sampling. To test the monophyly of the section as well as to clarify interspecific relationships, the nuclear ribosomal DNA internal transcribed spacer(nrDNA ITS) and three chloroplast sequences (ndhF-rlp32, rpl32-trnL(UAG), and trnG(UCC)-trnS(GCU)) were employed. Phylogenetic analyses were performed by maximum likelihood and Bayesian inferences. The results showed that O.sect. Onobrychis is monophyletic and composed of two main well-supported clades which are redefined as two subsections (O.subsect. Onobrychis, O. subsect. Macropterae).Ancestral character reconstruction of morphological traits: life form, wing to standard ratio, chromosome number, and ploidy level, indicated that short-winged petal is a synapomorphy for a group of species in the section while other traits have undergone parallel evolution. Possessing the basic chromosome number x= 7 has arisen twice, independently. It seems that perenniality and polyploidy are probably the key innovations in the diversification of O. sect. Onobrychis.